Determinants of linguistic and communicative competence of second language learners of English in the University of the Philippines Integrated School - Pastrana, Cecilia Laserno Cantero 1929-
This study attempted to relate Filipino learner factors to second language achievement. The findings of the study showed that intelligence, surgency and dependability correlate highly and positively with communicative competence. The findings tend to support previous research findings that communicative competence and linguistic competence are interrelated but separate constructs. The author recommends the reintensification of the teaching of grammar in Philippine ESL classrooms.